The African Academy of Sciences - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
The African Academy of Sciences (AAS) which is based in Nairobi Kenya, was founded in 1985 to pro mote and foster the growth of the scientific community in Africa. The objectives of the Academy are to stimulate, design and coordinate regional,...